Floristic Account of Apocynaceae (Gentianales) in Tunisia: New Additions to National and North African Flora with Nomenclatural Updates and Taxonomic Notes - Ridha El Mokni; Duilio Iamonico (Plants, 2025)
A taxonomic revision of the family Apocynaceae (Gentianales) from Tunisia is presented. Field surveys carried out during the last two decades allowed us to identify new records at the national level, i.e., Asclepias curassavica, Carissa macrocarpa, Cascabela thevetia, and Cryptostegia grandiflora (the latter three are new to the non-native Mediterranean and North African woody vascular flora). The genus Asclepias is new at a national level, whereas Carissa, Cascabela, and Cryptostegia are recorded here for the first time in the Mediterranean basin. Information is provided about nomenclature (accepted names, main synonyms, and types), morphology, chromosome number, chorology, occurrence in Tunisia, habitat, phenology, and taxonomic annotations, and original photos are prepared. Diagnostic keys relating to generic and species ranks are also given. Using typificitions, the identity of the Linnaean names Cynanchum erectum and C. monspeliensis, Pourret’s Vinca difformis, and Roxburgh’s Nerium grandiflorum is discussed.